2008
DOI: 10.3141/2075-01
|View full text |Cite
|
Sign up to set email alerts
|

Operating Speed Prediction Models for Horizontal Curves on Rural Four-Lane Highways

Abstract: Previous studies documented that a uniform design speed does not necessarily guarantee design consistency on rural two-lane facilities. Since a similar process is also followed for four-lane rural highways, it is reasonable to assume that similar inconsistencies could be found on such roadways. The operating speed-based method has been extensively used in other countries as the primary method to examine design consistency. Numerous studies have been completed on rural two-lane highways for predicting operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 10 publications
4
23
0
Order By: Relevance
“…It has been found that fatal crashes in horizontal curves are approximately one fourth of the total fatal crashes on highways (Torbic et al 2004;Fitzsimmons et al 2012;Fitzsimmons et al 2013a;Campbell et al 2012;Glennon et al 1983). However, the fatal crash per unit length of curve sections (i.e., total crashes at curves/ total length of curve sections) is higher than the fatal crash per unit length of tangent sections (i.e., total crashes at tangents/total length of tangent sections) of the highway (Torbic et al 2004;Gong, Stamatiadis 2008). Most of the fatal crashes in horizontal curves are single-vehicle crash (Glennon et al 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that fatal crashes in horizontal curves are approximately one fourth of the total fatal crashes on highways (Torbic et al 2004;Fitzsimmons et al 2012;Fitzsimmons et al 2013a;Campbell et al 2012;Glennon et al 1983). However, the fatal crash per unit length of curve sections (i.e., total crashes at curves/ total length of curve sections) is higher than the fatal crash per unit length of tangent sections (i.e., total crashes at tangents/total length of tangent sections) of the highway (Torbic et al 2004;Gong, Stamatiadis 2008). Most of the fatal crashes in horizontal curves are single-vehicle crash (Glennon et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The Highway Capacity Manual (TRB 2010) suggests that vehicles travelling with headway equal to or greater than a threshold headway value are considered as free flowing. For rural highways, several researchers have adopted the threshold headway value as 5 s (Fitzpatrick et al 2000a;Hashim et al 2016;Gong, Stamatiadis 2008;Poe et al 1996;Russo et al 2015Russo et al , 2016. However, weak lane discipline in multi-lane divided highways can influence vehicles (Mathew et al 2015;Mallikarjuna, Rao 2011;Gunay 2003Gunay , 2007Bangarraju et al 2016;Drew 1968;Case et al 1953;May 1959;Rawson 2015) prior to centre of the horizontal curve.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies by Chiguma [8], Ghani et al [9], Al-Kaisy & Karjala [10] and Ministry of Works Malaysia [11] also adopted the same headway threshold of 8 seconds. Meanwhile, other studies conducted by Tseng et al [3], Figueroa & Tarko [12], Gong and Stamatiadis [13], Himes and Donnell [14], Saifizul et al [15] and Sekhar et al [16] have measured the speed of free-flow vehicles based on time headways of 5 seconds while Silvano and Bang [17] have used headway threshold value of 10 seconds to measure free-flow speed. However, Wu et al [18] have adopted a longer threshold value of 12 seconds to investigate the difference between free driving and car following.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies have dealt with drivers' behaviour on horizontal curves. Horizontal curves, which provide the link between two or more tangents have been identified as an important cause of vehicle crashes [2]. There are several reasons that horizontal curves become an integral part of the roadway as highlighted by Diew [3].…”
Section: Introductionmentioning
confidence: 99%